Chronic relapsing cutaneous leishmaniasis in an elderly female: A rare clinical presentation from a nonendemic area - Shagufta Rather; Safia Bashir; Y J Bhat; Iffat Hassan (Wolters Kluwer Medknow Publications, 2019)
The presentation of cutaneous leishmaniasis (CL) varies from asymptomatic erythematous papules to nodulo-ulcerative forms over the exposed parts of body, generally healing slowly in 3-12 months. Besides, rare and atypical presentations of disease are being reported that pose both a diagnostic and therapeutic challenge especially in nonendemic areas. There has been an increase in the incidence of CL in our region over the past decade, and most of our patients belong to district Kupwara which is the north-most district of Kashmir valley, situated at an altitude of 5300 feet above sea level sharing borders with Pakistan-administered Kashmir. Herein, we report a case of an elderly female from a nonendemic area who had a relapse of cutaneous disease at a previously treated site and came to us with an atypical presentation of more than 2 years duration.